What are the underlying factors for the severity of cyclic mastalgia? - Soheila Nazarpour; Masoumeh Simbar; Zahra Kiani; Neda Khalaji; Mobina Khorrami Khargh (PLoS ONE, 2025)
Background Cyclic Mastalgia (CM) is the most common breast complaint among reproductive-aged women and can affect their quality of life. The exact etiology is not completely understood, but several factors are suggested to be effective. This study aimed to assess the relationship of some possible related factors with CM. Methods This cross-sectional study was conducted on 335 female students with severe cyclic Mastalgia. They were selected by multi-stage sampling method from dormitories of Shahid Beheshti University of Medical Sciences in Tehran-Iran. Data was collected using an online questionnaire including the Beck’s Depression Inventory, the Spielberger Anxiety Inventory, the Fisher Body-Image Questionnaire, the Cardiff Breast Pain Chart (NDBP), and a socio-demographic questionnaire. The data were analyzed by SPSS 29 and using Spearman, Mann-Whitney, Kruskal-Wallis, and multiple linear regression tests. Results The average age of the participants was 25.61 ± 5.92 years with a Cardiff score of 31.76 ± 4.33 (mean ± SD). The mean scores for body image, anxiety, and depression were 159.33 (±37.62), 43.35 (±10.32), and 10.80 (±9.79), respectively. Beck’s depression score had a significant positive correlation with the severity of CM (P = 0.035). A significant positive correlation was also found between smoking and the severity of CM (P = 0.035, r = 0.115). There were significant positive correlations between the severity of CM with the duration of the menstrual cycle (P < 0.001) and menstruation (P = 0.001). There were no significant relationships between the severity of CM with other variables. The multiple linear regression test demonstrated that depression (P = 0.014) and duration of the menstrual cycle (P = 0.001) are predictors of severity of CM. Conclusion Depression and duration of menstrual cycle are potential predictors of the severity of CM. Promotion of Women’s menstrual and mental health as well as prevention of high-risk habits such as smoking should be considered for the severity of CM and improving the quality of life.